Perception and Action in Sports. On the Functionality of Foveal and Peripheral Vision - Klostermann, André; Vater, Christian; Kredel, Ralf; Hossner, Ernst-Joachim (Frontiers in Sports and Active Living, 2020)
An optimal coupling between perception and action is crucial for successful performance in sports. In basketball, for example, a stable fixation onto the basket helps to gain precise visual information of the target to successfully throw a basketball into the basket. In basketball-defense situations, however, opposing players cutting to the basket can be detected by using peripheral vision as less precise information are sufficient to mark this player. Those examples elucidate that to solve a given task foveal and peripheral vision can be used to acquire the necessary information. Following this reasoning, the current state of our framework will be presented that allows one to predict the functionality of one or the other or both depending on the current situation and task demands. In more detail, for tasks that require high motor precision like in far-aiming tasks, empirical evidence suggests that stable foveal fixations facilitate inhibitory processes of alternative action parameterization over movement planning and control. However, more complex situations (i.e., with more than one relevant information source), require peripheral vision to process relevant information by positioning gaze at a functional location which might actually be in free space between the relevant information sources. Based on these elaborations, we will discuss complementarities, the role of visual attention as well as practical implications.